Geological Carbon Sequestration by Reactive Infiltration Instability - Sun, Yizhuo; Payton, Ryan L.; Hier-Majumder, Saswata; Kingdon, Andrew (Frontiers in Earth Science, 2020)
We study carbon capture and sequestration (CCS) over time scales of 2000 years by implementing a numerical model of reactive infiltration instability (RII) caused by reactive porous flow. Our model focuses on the mineralization of CO2dissolved in the pore water---the geological carbon sequestration (GCS) phase of a CCS operation---starting 10--100 years after the injection of CO$_2$ in the subsurface. We test the influence of three parameters: porosity, mass fraction of the Ca-rich feldspar mineral anorthite in the solid, and the chemical reaction rate, on the mode of fluid flow and efficiency of CaCO3 precipitation during GCS. We demonstrate that the mode of porous flow switches from propagation of a planar front at low porosities to propagation of channels at porosities exceeding 10%. The channels develop earlier for more porous aquifers. Both high anorthite mass fraction in the solid and high reaction rate aid greater amounts of carbonate precipitation, with the reaction rate exerting the stronger influence of the two. Our calculations indicate that an aquifer with dimensions 500 m X 2 km X 2 km can sequester over 350 Mt solid CaCO3 after 2000 years. c3. To precipitate 50 Mt CaCO3 after 2000 years in this aquifer, we suggest selecting a target aquifer with more than 10 wt% of reactive minerals. We recommend that the aquifer porosity, abundance of reactive aluminosilicate minerals such as anorthite, and reaction rates are taken into consideration while selecting future CCS sites.